Anti-inflammatory and Anti-oxidative Effects of Phytohustil® and Root Extract of Althaea officinalis L. on Macrophages in vitro - Bonaterra, Gabriel A.; Bronischewski, Kevin; Hunold, Pascal; Schwarzbach, Hans; Heinrich, Ennio-U.; Fink, Careen; Aziz-Kalbhenn, Heba; Müller, Jürgen; Kinscherf, Ralf (Frontiers in Pharmacology, 2020)
Introduction: The medicinal plant marshmallow (Althaea officinalis L.), that has been known for many centuries, is used for the treatment of cough. Application of medicinal extracts of marshmallow roots shows immediate effects like a protective film on the inflamed mucosa. Because the soothing layer of marshmallow reduces irritation of the mucous system, a faster regeneration is supported by defense mechanisms required to protect the respiratory tract from environmental injury. Macrophages (MΦ), which belong to a group of multipurpose defensive cells, provide the first line of defense against mucosal invasive pathogens. The present study was performed to investigate, whether the herbal medicinal product have anti-inflammatory or anti-oxidative effects on pro-inflammatorily activated MΦ or after oxidative stress induction, with special attention to elucidate their effects on the mechanism of intracellular defense as well as on their migratory capacity. Results: Treatment of PMA-differentiated human THP-1 MΦ with Phytohustil® increased their viability without affecting the cell number. Phytohustil® or root extracts of Althaea officinalis (L) – an active component of Phytohustil® - were able to protect human THP-1 MΦ against H2O2-induced cytotoxicity and H2O2-induced ROS production. Moreover, Phytohustil®, root extracts of Althaea officinalis (L) or diclofenac used as anti-inflammatory reference substance, inhibited the LPS-induced release of tumor necrosis factor (TNF) as well as of IL6 in human THP-1 MΦ. Treatment of human THP-1 MΦ with Phytohustil®, its excipients or root extracts of Althaea officinalis (L) didn´t impair the mitochondrial membrane potential (MMP). Finally, Phytohustil®, and root extract of Althaea officinalis (L.) activated the migratory capacity of human THP-1 MΦ. Conclusions: The present in vitro investigations indicate protective, i.e. anti-oxidative and anti-inflammatory effects of root extracts of Althaea officinalis (L.) and Phytohustil®, additionally improving the migratory capacity of MΦ. These anti-inflammatory effect were similar or even better than effects of diclofenac. Thus, our data support and may explain the positive effect of Phytohustil® observed in patients during the therapy of inflamed buccal mucosal membranes and against the adverse effects of cough.